2014
DOI: 10.1007/s00382-014-2359-2
|View full text |Cite
|
Sign up to set email alerts
|

The stratospheric wintertime response to applied extratropical torques and its relationship with the annular mode

Abstract: and the long-term response is less NAM-like and no longer easterly at high latitudes. This is consistent with ray theory and differences in climatological u between the two types of simulations. The response to a tropospheric wave forcing perturbation is also NAM-like. These results suggest that dynamical feedbacks tend to make the long-term NH extratropical stratospheric response to arbitrary external forcings NAM-like, but only if the feedbacks are sufficiently strong. This may explain why the observed polar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 67 publications
2
12
1
Order By: Relevance
“…Recently, some studies revealed possible compensation of PW drag of the middle atmospheric circulation by parameterized OGWs in general circulation models (McLandress and McFarlane 1993;Cohen et al 2013Cohen et al , 2014Sigmond and Shepherd 2014;Watson and Gray 2015). Our results show that taking account of OGW parameterization can both decrease or increase wave amplitudes, EP-fluxes, and wave drag of the mean flow depending on the considered PW modes.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Recently, some studies revealed possible compensation of PW drag of the middle atmospheric circulation by parameterized OGWs in general circulation models (McLandress and McFarlane 1993;Cohen et al 2013Cohen et al , 2014Sigmond and Shepherd 2014;Watson and Gray 2015). Our results show that taking account of OGW parameterization can both decrease or increase wave amplitudes, EP-fluxes, and wave drag of the mean flow depending on the considered PW modes.…”
Section: Discussionmentioning
confidence: 62%
“…Many studies were devoted to the generation of PW modes in the middle atmosphere by horizontally inhomogeneous gravity wave drag (e.g., Holton 1984;McLandress and McFarlane 1993;Watson and Gray 2015). Using the MUAM, Gavrilov et al (2013a, b) simulated the generation of PW modes by inhomogeneous OGW forcing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This includes prescribed ozone fields following Cionni et al [2011] and fixed atmospheric concentrations of carbon dioxide (CO 2 ), methane (CH 4 ), and nitrous oxide (N 2 O). Except for the process of methane oxidation, HadGEM2-CCS does not include stratospheric chemistry but does include a well-resolved stratosphere capable of internally generating a realistic QBO Watson and Gray, 2014]. The internal QBO is forced by parameterized orographic and nonorographic gravity wave drag schemes [Martin et al, 2011].…”
Section: Modelmentioning
confidence: 99%